2021
DOI: 10.1029/2020ja028877
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Two‐Day Waves in the Northern Hemisphere Observed by TIMED/SABER Measurements During 2002–2019

Abstract: The quasi‐two‐day waves (QTDWs) with westward‐propagating wavenumbers 2 (W2), 3 (W3), and 4 (W4) during the boreal summers were statistically examined using TIMED/SABER temperature observation datasets during 2002–2019 with a 6‐day two‐dimensional least‐squares fitting window. The W4 (W3) and W2 QTDWs were observed at ∼67–73 km and ∼30–40°N, and ∼89–95 km and ∼20–30°N, respectively. The W4 mode occurred 57 times over the past 18 years compared to 43 (52) times for the W3 (W2) QTDWs. The W4 QTDW reached maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They also found that the mean vertical wavelength of Q2DWs was approximately 30-40 km, which provided good conditions for its propagation from the source region to the upper atmosphere. Gu et al (2021) found that W3 and W4 occurred more frequently at approximately 48 hr, while W2 tended to be short-period events. In addition, they also found that the wave periods of W3 and W4 rise during the late NH summer.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…They also found that the mean vertical wavelength of Q2DWs was approximately 30-40 km, which provided good conditions for its propagation from the source region to the upper atmosphere. Gu et al (2021) found that W3 and W4 occurred more frequently at approximately 48 hr, while W2 tended to be short-period events. In addition, they also found that the wave periods of W3 and W4 rise during the late NH summer.…”
mentioning
confidence: 88%
“…Gu et al. (2021) found that W3 and W4 occurred more frequently at approximately 48 hr, while W2 tended to be short‐period events. In addition, they also found that the wave periods of W3 and W4 rise during the late NH summer.…”
Section: Introductionmentioning
confidence: 99%
“…The mesosphere and lower thermosphere (MLT) are transitional regions connecting the lower and upper atmosphere. Quasi-2-day waves (Q2DWs) are global-scale atmospheric oscillations that play a crucial role in the dynamics of the MLT [1][2][3][4][5]. Atmospheric waves induce horizontal and vertical couplings that critically affect momentum, energy, and chemical transport throughout the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Q2DWs have been identified at high latitudes as well as near the equator [2,4]. Mid-latitude Q2DWs exhibit distinct summer maxima characterized by one or several bursts, each lasting multiple weeks [1,3], whereas highlatitude Q2DWs demonstrate maximum activity during winter [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale gravity waves induced by the perturbation in the lower atmosphere propagate upwards into the MLT region, leading to acceleration/deceleration of background winds and variations in the thermal structure and general circulation by breaking or dissipation of GWs. Interannual variations such as the SAO [12,13], QBO [14], short-period oscillations of 3 to 15 days [15][16][17][18], and ISO variations with periods between 30 and Atmosphere 2023, 14, 1034 2 of 14 100 days [19][20][21][22][23] have been suggested to be able to impact atmospheric variability in the MLT region. The QBO in the lower stratosphere is modulated by convectively generated waves such as gravity waves, Rossby gravity, and Kelvin [24][25][26], whereas KW and GW are considered to be important for driving the SAO [27,28].…”
Section: Introductionmentioning
confidence: 99%